PENGARUH STRES KERJA DAN TURNOVER TERHADAP KINERJA KARYAWAN PADA PT PRIMADAYA PLASTISINDO TBK BOGOR - JAWA BARAT - Muhammad Ilyas; Rima Handayani (Journal of Research and Publication Innovation, 2025)
This study aims to examine the influence of work stress and Turnover on employee performance at PT Primadaya Plastisindo, Tbk Bogor - West Java, both partially and simultaneously. The research uses a quantitative method with a sample of 91 employees, selected through non-probability sampling using the Slovin technique. The data used includes primary and secondary data, obtained through observation, documentation, questionnaires, and literature review. Data analysis is conducted using multiple linear regression, covering instrument tests, classical assumption tests, linear regression tests, correlation and determination coefficients, as well as partial and simultaneous hypothesis testing. The results show that work stress has a negative and significant effect on employee performance with a t-value of -2.082>1.987 (t-table) and a significance of 0.040<0.05. Turnover has a positive and significant effect with a t-value of 9.102>1.987 (t-table) and a significance of 0.000<0.05. Simultaneously, work stress and Turnover also have a positive and significant effect on performance with an F-value of 171.877>3.10 (F-table) and a significance of 0.000<0.05. The determination coefficient shows that work stress and Turnover simultaneously influence employee performance by 79.6%, while the remaining 20.4% is influenced by other factors not tested in this study.